The Role of Empathy in Alcohol Use of Bullying Perpetrators and Victims: Lower Personal Empathic Distress Makes Male Perpetrators of Bullying More Vulnerable to Alcohol Use - Prignitz, Maren; Banaschewski, Tobias; Bokde, Arun L. W.; Desrivières, Sylvane; Grigis, Antoine; Garavan, Hugh; Gowland, Penny; Heinz, Andreas; Martinot, Jean-Luc; Paillère Martinot, Marie-Laure; Artiges, Eric; Poustka, Luise; et al. (MDPI, 2023)
Bullying often results in negative coping in victims, including an increased consumption of alcohol. Recently, however, an increase in alcohol use has also been reported among perpetrators of bullying. The factors triggering this pattern are still unclear. We investigated the role of empathy in the interaction between bullying and alcohol use in an adolescent sample (IMAGEN) at age 13.97 (±0.53) years (baseline (BL), N = 2165, 50.9% female) and age 16.51 (±0.61) years (follow-up 1 (FU1), N = 1185, 54.9% female). General empathic distress served as a significant moderator of alcohol use in perpetrators (F9, 493 = 17.978, p < 0.01), which was specific for males and FU1. Male perpetrators, who are generally less sensitive to distress, might thus be more vulnerable to alcohol abuse.
DOI der ursprünglichen Veröffentlichung: 10.3390/ijerph20136286